mtan's e then show that (1+2) + (x ...
Question
Fullscreen

mtan's e then show that (1+2) + (x - m 4, so

11th - 12th Class
Maths
Solution
95
Rating
4.0 (1 ratings)
Fullscreen
( y=e^{m tan ^{+} x} ) ( y_{1}=frac{d y}{d x}=e^{operatorname{mitan}^{+} x} cdot frac{m}{1+x^{2}} ) ( Rightarrow y_{1}=frac{y m}{1+x^{2}} ) ( Rightarrowleft(1+x^{2}right) y_{1}=y m ) Differentiatif again ( left(1+x^{2}right) y_{2}+2 x y_{1}=m y_{1} ) ( Rightarrowleft(1+x^{2}right) y_{2}+(2 x-m) y_{1}=0 ) Hence, proved.
Quick and Stepwise Solutions Just click and Send Download App OVER 20 LAKH QUESTIONS ANSWERED Download App for Free